Outorga onerosa em Goiânia: a verticalização no bairro Negrão de Lima - Silva, Elaine Neves da (2018)
Brazil has a legal device that distinguishes building rights from the right to property. Due to this device, the government is attributed the property over building rights, which can be sold to whoever wishes to buy it. It is called “outorga onerosa do direito de construer” (Portuguese for “issuance of building rights over payment”, OODC for short) and it has been largely used by the real estate sector on Negrão de Lima, a neighborhood in Goiânia, state of Goiás. This legal device allows construction of buildings taller than the average limit up to the maximum coefficient established by the city’s land-use planning and it has immensely transformed the local landscape. It has also transformed the neighborhood dramatically, making it more demographically dense in a short period of time, which has been an object of concern for many scholars of the area of urbanism. This social phenomenon and the scarcity of specific literature on the issue has led us to realize the urgency and the relevance of the theme, leading to a study that aims to show the implications of the aforementioned legal device in the production of urban space and the transformation of the local landscape. The qualitative research and the analytical study are based on the empiric knowledge of the place, documentation studies, and observations of how the soil has been occupied from 2006 to 2017. The latter was possible due to the analysis of aerial images of the region within this period, which makes it possible to compare the neighborhood’s situation before and after OODC.